PENGARUH PEMBERIAN LARUTAN NaCl TERHADAP PERTUMBUHAN TANAMAN SELEDRI (APIUM GRAVEOLOENS L.) - SUKERTA, I MADE; SUMANTRA, I KETUT; RAMDHOANI, RAMDHOANI; SUARSANA R., I WAYAN (GANEC SWARA, 2024)
This research is entitled "The Effect of Giving NaCl Solution on the Growth of Celery Plants (Apium Graveoloens L.)". The purpose of this research is to determine the response to the growth of celery plants with the application of NaCl solution and to determine the appropriate concentration of solution to provide the best response to the growth and yield of celery plants. This research was conducted for three months starting from October 2023 to December 2023. The method used in this research was the Randomized Group Design (RAK) method with six treatments, namely 0 g/1 L salt water treatment (NaCl 0), treatment salt 1.5 g/1 L water (NaCl 1), salt treatment 3 g/1 L water (NaCl 2), salt treatment 4.5 g/1 L water (NaCl 3), salt treatment 6 g/1 L air (NaCl 4), salt treatment 7.5 g/1 L water (NaCl 5) with four repetitions. The results of the research showed that the use of NaCl solution has a very real influence on the parameters of plant height, number of stalks, number of tillers, root length, plant fresh weight and oven dry weight. With other treatments shown by the average number of observation parameters, the highest results were shown in the fifth treatment (NaCl 4), namely the average plant height was 44.30/cm, number of leaves was 47.25/piece, number of stalks was 9, 75/stem, number of tillers 3.00/stem, root length 19.13/cm, total fresh weight of plant 32.25/g, oven dry weight of plant 14.50/g.